1994
DOI: 10.1128/jvi.68.11.7448-7457.1994
|View full text |Cite
|
Sign up to set email alerts
|

Sequence requirements for stable binding and function of Rep68 on the adeno-associated virus type 2 inverted terminal repeats

Abstract: Replication of the palindromic inverted terminal repeats (ITRs) of adeno-associated virus type 2 requires several functions of the viral nonstructural Rep proteins. These include binding to the ITR, nicking of the double-stranded replication intermediate at the terminal resolution site (trs), and then strand displacement and synthesis from the nick. This report demonstrates the ability of both recombinant fusion maltose-binding protein (MBP)-Rep68A produced in Escherichia coli and wild-type (wt) Rep68 to bind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
78
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 48 publications
12
78
1
Order By: Relevance
“…Our deletion analyses indicated that the P 5 promoter region between the TATA box and the transcription initiation site is important for the negative regulation by Rep68. This region is similar to the RRSs identified previously in the AAV ITR and in the AAV integration site in human chromosome 19, which contain three perfect GAGC repeats and are bound by Rep proteins (12,13,22,23,42,56). Although the P 5 RRS contains only one perfect GAGC box, it is bound by Rep68, as shown by the gel shift analyses.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our deletion analyses indicated that the P 5 promoter region between the TATA box and the transcription initiation site is important for the negative regulation by Rep68. This region is similar to the RRSs identified previously in the AAV ITR and in the AAV integration site in human chromosome 19, which contain three perfect GAGC repeats and are bound by Rep proteins (12,13,22,23,42,56). Although the P 5 RRS contains only one perfect GAGC box, it is bound by Rep68, as shown by the gel shift analyses.…”
Section: Discussionsupporting
confidence: 79%
“…3B). The effect of the length of the fragment in stabilizing Rep binding has also been observed with the linear ITR DNA by using a purified maltose-binding protein-Rep68 fusion protein (13). Consequently, all of the oligonucleotide pairs analyzed in band shift analyses were cloned into pBluescript and tested as larger fragments.…”
Section: Localization Of a Negativementioning
confidence: 99%
“…Within the ITR region, two elements have been described which are central to the function of the ITR, a GAGC repeat motif and the terminal resolution site (TRS). The repeat motif has been shown to bind Rep when the ITR is in either a linear or a hairpin conformation (15,16,44). This binding serves to position Rep68/78 for cleavage at the TRS, which occurs in a site-and strand-specific manner.…”
mentioning
confidence: 99%
“…There are three salient features of the AAV ITR that are required for vector production: (i) a 16-nucleotide tetrameric repeat (GAGC) sequence that is specifically bound by the Rep68/78 proteins termed the Rep-binding element (RBE), (ii) a sequence within the ITR internal hairpin that serves to orient Rep68/78 towards its resolution site termed RBE' (45)(46)(47)(48)(49), and (iii) the terminal resolution sequence (trs), which is the site of the strand-specific Rep68/78 endonuclease activity (44,(50)(51)(52). The N-termini of the larger Rep proteins contain a DNA-binding domain, as well as strand-specific endonuclease activity, necessary for initiating replication during virion production and site-specific integration (46,(53)(54)(55)(56). The C-terminal portion of Rep68/78 is required for multimerization and confers helicase activity which, in part, extrudes a putative nicking stem within the ITR sequence (54,57,58).…”
Section: Adeno-associated Virus Genomementioning
confidence: 99%